Effectiveness of Service in the Education Process for the Formation of Police NCOs at the Gorontalo Regional Police State Police School (SPN) - Modanggu, Djalaludin; Sulila, Ismet; Isa, Rusli (Abdurrauf Science and Society, 2025)
This study aims to evaluate the effectiveness of services in the education process of forming Bintara Polri at the State Police School (SPN) Polda Gorontalo based on three main dimensions of the theory of effectiveness according to Steers, namely goal achievement, integration, and adaptation. The method used in this study is a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, and documentation studies. The main focus of this study is to examine and describe the extent to which academic services at SPN Polda Gorontalo have achieved institutional goals, built integration between units, and demonstrated adaptive capacity to change. The results of the study indicate that in the dimension of goal achievement, services in the education process of forming Bintara Polri at SPN Polda Gorontalo have a clear goal of forming competent and disciplined serdik, but its achievement is still constrained by the high level of remedial and irregular schedules. Planning and evaluation have been carried out, but have not been able to close the competency gap. Integration between internal sections is going quite well, but external cooperation and the use of information technology are still very limited, hampering innovation and academic renewal. In terms of adaptation, instructor recruitment and placement have not fully considered academic competence, the response to regulatory changes is still slow, and facilities and training are not evenly distributed. Overall, SPN Polda Gorontalo needs to strengthen learning strategies, external collaboration, and development of HR capacity and learning facilities to improve the quality of service in the education process of forming Bintara Polri as a whole.